2015
DOI: 10.1083/jcb.201505011
|View full text |Cite
|
Sign up to set email alerts
|

Shootin1–cortactin interaction mediates signal–force transduction for axon outgrowth

Abstract: The shootin1–cortactin interaction participates in netrin-1–induced F-actin–adhesion coupling and in the promotion of traction forces for axon outgrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(116 citation statements)
references
References 63 publications
4
111
0
1
Order By: Relevance
“…These mass spectrometry data confirm that SHOT1 is phosphorylated by YopO at Ser249, which contains the canonical PAK phosphorylation sequence (K/R-R-X-p[S/T])26. Given the structural similarity of YopO’s kinase domain with PAKs, we assayed whether PAKs (in this case PAK4) can phosphorylate other substrates of YopO (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…These mass spectrometry data confirm that SHOT1 is phosphorylated by YopO at Ser249, which contains the canonical PAK phosphorylation sequence (K/R-R-X-p[S/T])26. Given the structural similarity of YopO’s kinase domain with PAKs, we assayed whether PAKs (in this case PAK4) can phosphorylate other substrates of YopO (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 65%
“…PKD1 phosphorylates VASP at Ser153 and Ser319 (numbering for mouse, Ser157 and Ser322 in human), and in contrast, increases F-actin polymerization and reduces VASP localization at focal adhesions43. YopO phosphorylates SHOT1 at Ser249, which is also targeted by PAK1, and results in enhancing SHOT1’s interaction with cortactin at sites of dynamic actin assembly26.…”
Section: Discussionmentioning
confidence: 99%
“…[27] As discussed earlier, additional folic acid increased the expression of a marker of neuronal differentiation, microtubule-associated protein 2 (MAP-2), in PC-12 cells. Here, we explored whether the chemical stimuli by folic acid would not only increase the expression of cytoskeletal filaments such as microtubules, but also lead to higher cytoskeletal tension, thus increasing cellular traction forces.…”
Section: Resultsmentioning
confidence: 98%
“…Growth cones exhibit F-actin RF similar to cells migrating on ECM [5153] and clutching of RF is thought to regulate the rate and direction of axon extension [5459]. Evidence from several laboratories has shown that the rate of RF is directly related to substratum traction forces [6062] and inversely related to the rate of growth cone advance [54, 63].…”
Section: Growth Cone Point Contact (Pc) Adhesions Regulate Axon Outgrmentioning
confidence: 99%